Nazarana Easy Tailor / Norfariza Azhbi... [et al.] - Suhud, Nazirah; Mohd Jamil, Nurul Amira; Abduleasid, Sitti Ridzna; Azhbi, Norfariza (2013)
Nazarana Easy Tailor providing tailoring services for the citizens. The specialty of our company is that we sewing variety types of clothes for the customers. The business begin operate on fifth January 2014. Nazarana Easy Tailor is a partnership contract consists of five members which are Norfariza binti Azhbi, Nurul Amira binti Mohd.Jamil, Sitti Ridzna binti Abduleasid and Nazirah binti Suhud. Each members contribute capital 25% which is RM 25 000. The location of Nazarana Easy Tailor is at Alamesra. It is because Alamesra near to the housing area, workplace and shopping mall. This can attract more customers to come to our shop. In marketing plan, our specific target is at Alamesra. Nazarana Easy Tailor divides their target market based on the demographic segmentations which are students, housewife, visitors, working people and tourists. The market strategies that we used is implementing 4Ps concept. The 4Ps concept consists of products (services), pricing, promotion and place strategy. For the operating plan, we start to operate in nine in the morning until nine evening for Monday to Saturday. But for Sunday, we only operate half day which means that we start in nine mornings until three evening. Our company provides different types of clothes based on the customers wants. We also provide to sewing clothes for the events. In the first and second month, Nazarana Easy Tailor estimated will incurred loss. This is because our company needs to use a lot of money to buy the materials for the operation. However, Nazarana Easy Tailor estimated profits begin from the third month until the next years. As mention before, the main attraction of Nazarana Easy Tailor is the sewing variety of clothes. According to financial position, our company can going further of their business. Our company can expand business on the market size so that company wills more success in the future.